Impact of fetal endoscopic tracheal occlusion in fetuses with congenital diaphragmatic hernia and moderate lung hypoplasia. (16th June 2021) - Cruz‐Martínez, Rogelio; Shazly, Sherif; Martínez‐Rodríguez, Miguel; Gámez‐Varela, Alma; Luna‐García, Jonahtan; Juárez‐Martínez, Israel; López‐Briones, Hugo; Coronel‐Cruz, Fausto; Villalobos‐Gómez, Rosa; Ibarra‐Rios, Daniel; Ordorica‐Flores, Ricardo; Nieto‐Zermeño, Jaime
Abstract: Objective: To assess the effect of Fetal Endoscopic Tracheal Occlusion (FETO) on neonatal survival in fetuses with left congenital diaphragmatic hernia (CDH) and moderate lung hypoplasia. Study Design: CDH fetuses with moderate pulmonary hypoplasia (observed/expected lung area to head ratio between 26% and 35%, or between 36% and 45% with liver herniation) were prospectively recruited. Included patients were matched to a control group who were ineligible for FETO. Primary outcomes were survival at 28 days, at discharge, and at 6 months of age, respectively. Results: 58 cases were recruited, 29 treated with FETO and 29 matched controls. Median gestational age (GA) at balloon placement and removal were 29.6 and 33.6 weeks, respectively. FETO group showed significantly lower GA at delivery (35.2 vs. 37.1 weeks, respectively, p < 0.01), higher survival at 28 days (51.7 vs. 24.1%, respectively, p = 0.03), at discharge (48.3 vs. 24.1%, respectively, p = 0.06), and at six months of age (41.4 vs. 24.1%, respectively, p = 0.16), and significantly lower length of ventilatory support (17.8 vs. 32.3 days, p = 0.01) and NICU stay (34.2 vs. 58.3 days, p = <0.01) compared to controls. Conclusion: FETO was associated with a non‐significant increase in survival and significantly lower neonatal respiratory morbidity among CDH fetuses with moderate lung hypoplasia. Key Points: What's already known about this topic? Fetal endoscopic tracheal occlusion (FETO) has shown an improvement on neonatal survival in fetuses with severe lung hypoplasia. Fetuses with congenital diaphragmatic hernia and moderate lung hypoplasia, that is those with O/E‐LHR between 26% and 35% or between 36% and 45% and liver herniation, are associated with survival rates around 50%. What does this study add? This investigation represents the first study to support the role of FETO in fetuses with left sided CDH and moderate lung hypoplasia. According to our data, a non‐significant increase in survival and a significantly lower neonatal respiratory morbidity were observed in fetuses who underwent FETO compared to those who were managed expectantly and treated with standard postnatal management.